Youth Disillusionment and Its Impacts on Political and Social Structures: A Case Study of Youth Movements in Thailand and China - Tieojaroenkit, Tinnapop; Lerdtomornsakul, Unisa (Journal of Social Work and Social Administration, 2024)
This article aims to study and analyze the causes of the youth disillusionment trend in Thailand and China through a comparative approach. The analysis will concentrate on specific factors and unique causes in Thailand that contribute to the disillusionment of the new generation and lead to their involvement in political offenses. The study investigates the factors contributing to the disillusionment among the new generation in Thailand and China using research methodologies grounded in academic exploration and relevant literature, including academic journals, research papers, and theses. The study employs criminological concepts, specifically Social Structure Theories, Social Bond Theory along with the concept of social media and influencer. Moreover, the researcher has collected data to analyze the factors contributing to the disillusionment of the new generation in Thailand and China. According to the study, it was found that the factors contributing to the disillusionment of the new generation in Thailand and China are similar in terms of political awareness, economic inequality, and the influence of social media. However, there are differences in forms of government. Nonetheless, issues such as generation gaps, mental health problems, stress among the new generation, and family upbringing can impact their disillusionment. Therefore, the government should implement proactive measures by reforming education and encouraging self-directed learning among the new generation.